An observation of using digital technology approach in students’ project presentation / Ellyana M.M.T - Ellyana, M.M.T; Mohd Zaki, M.F; Noraziah, Mohd Razali; Clement, Jimel (Universiti Teknologi MARA, Perak, 2018)
Technology is increasingly being utilized in higher education environments. Smart phones, computers, and other sophisticated devices are used in both teaching and learning situations. These devices and associated software are also seen as significantly helping students execute their ideas and express their creativity. This study uses a pilot survey to record the responses of students who utilize digital technology to create a project presentation. Questionnaires were utilised to achieve this objective in a quantitative manner by evaluating the level of happiness among students. In a qualitative manner, 35 respondents agree that the use of digital technology and software is preferable to a conventional oral class presentation, increasing students’ creativity and confidence.